STAPHYLOCOCCAL ENTEROTOXINS IN DOMESTIC CATS: AN UNDEREXPLORED RISK TO HUMAN HEALTH - Faisal Aftab; Luxshika Tharmarajah (Buletin Veteriner Udayana, 2026)
Companion animals, especially domestic cats, are known to be colonized by Staphylococcus aureus, which produces exotoxins known as staphylococcal enterotoxins (SEs). However, the role of cats as reservoirs of enterotoxin-producing strains and their impact on human health remain insufficiently understood. This study narratively reviewed existing literature to examine the relationship between feline-associated S. aureus and the effects of SEs on human health. Findings indicate that cats can harbor S. aureus in multiple anatomical sites and act as asymptomatic carriers, with some isolates possessing enterotoxin genes such as sea, seb, and sec. Evidence also suggests potential bidirectional transmission between cats and humans, particularly in close-contact environments. The stability and superantigenic properties of SEs contribute to their role in foodborne illness and immune-mediated conditions. However, most studies focus on gene detection rather than active toxin production, and direct evidence linking feline-associated strains to human disease remains limited. These findings highlight a potential zoonotic risk and emphasize the need for a One Health approach to surveillance and prevention.